2019
DOI: 10.1038/s41560-019-0457-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective high-temperature CO2 electrolysis enabled by oxidized carbon intermediates

Abstract: High-temperature CO2 electrolyzers offer exceptionally efficient storage of renewable electricity in the form of CO and other chemical fuels, but conventional electrodes catalyze destructive carbon deposition. Ceria catalysts are known carbon inhibitors for fuel cell (oxidation) reactions, however for the more severe electrolysis (reduction) conditions, catalyst design strategies remain unclear. Here we establish the inhibition mechanism on ceria and show selective CO2 to CO conversion well beyond the thermody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 61 publications
(90 reference statements)
3
68
0
2
Order By: Relevance
“…However, their specific characterizations have been comparatively limited because of technical difficulties related to the decrease of the electron mean-free path at elevated pressures 19 . Eventually, the progressive tools operable in realistic conditions 20,21 are necessarily required to unravel the early steps of CO 2 RR at the molecular level. Recently published literature supports the strong evidence of CO 2 activation beyond the pressure gap, for instance, the intramolecular bond-breakage phenomenon of CO 2 molecules was reported on the Cu 22,23 and Ni 24,25 catalysts at the elevated pressures.…”
mentioning
confidence: 99%
“…However, their specific characterizations have been comparatively limited because of technical difficulties related to the decrease of the electron mean-free path at elevated pressures 19 . Eventually, the progressive tools operable in realistic conditions 20,21 are necessarily required to unravel the early steps of CO 2 RR at the molecular level. Recently published literature supports the strong evidence of CO 2 activation beyond the pressure gap, for instance, the intramolecular bond-breakage phenomenon of CO 2 molecules was reported on the Cu 22,23 and Ni 24,25 catalysts at the elevated pressures.…”
mentioning
confidence: 99%
“…Graves et al recently demonstrated an interesting electrode where the current collector is substituted with Sr 0.99 Fe 0.75 Mo 0.25 O 3δ (SFM), and the catalytic activity is obtained with Pr-doped CeO 2 (CPO) nano particles [77]. Such an electrode could enable pressurized co-electrolysis of CO 2 and H 2 O, without Ni or Cu sintering, and without CH 4 formation.…”
Section: Renewable Methanolmentioning
confidence: 99%
“…Ceria has remarkable carbon‐suppression capability, Skafte et al. 27 studied on the surface properties of ceria and other vacancy rich oxides to further improve carbon tolerance and achieve stable and selective catalytic reactions of CO 2 .…”
Section: Development Of Soec Cathodes For Co2electrolysismentioning
confidence: 99%
“…Solutions include increasing the fuel electrode porosity and adjusting the operational conditions, while neither of them has been considered as better as replacing Ni-based material with some kinds of alternative cathode material. Ceria has remarkable carbon-suppression capability, Skafte et al [27] studied on the surface properties of ceria and other vacancy rich oxides to further improve carbon tolerance and achieve stable and selective catalytic reactions of CO 2 .…”
Section: Ni-basedmentioning
confidence: 99%